Prediction of Obsessive-compulsive Symptoms Based on Negative Affect, Rumination, and Dispositional Mindfulness - Afsaneh Mahmoudi; Rasoul heshmati; Majid Mahmoud Alilou (Universitas Ahmad Dahlan, 2020)
Obsessive-compulsive symptoms could be an important background for clinical disorder of OCD. The role of negative affect, rumination, and dispositional mindfulness has not been investigated in previous researches. Therefore, the purpose of this study was to study the relationship among negative affect, rumination, dispositional mindfulness with obsessive-compulsive symptoms. In a descriptive-correlational and crosses- sectional study, 283 students from University of Tabriz have selected by available sampling method during April through May 2017.Maudsley OCD inventory, Positive affect and negative affect scale (PANAS), Five Facet Mindfulness Questionnaire (FFMQ) and Rumination Scale of the Response Styles Questionnaire were used for collecting the data. Data were analyzed using Pearson correlation and multiple Regressions tests. The results showed that correlation between obsessive-compulsive symptoms and dispositional mindfulness was negative and significant, correlation between obsessive-compulsive symptoms and negative affect was positive and significant and correlation between obsessive-compulsive symptoms and rumination was significant. Also, negative affect, rumination, and dispositional mindfulness did able to predict the obsessive-compulsive symptoms. Dispositional mindfulness, negative affect, and rumination are the important determinants of obsessive-compulsive symptoms.